2021
DOI: 10.1371/journal.pone.0258186
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of hypofractionation with concomitant boost in patients with early breast cancer: A prospective study

Abstract: Aim To report the long-term local control and survival of patients with early breast cancer who had hypofractionated whole breast irradiation with concomitant boost (Hypo-CB). Methods and materials Between October 2009 and June 2010, 73 patients with early breast cancer (T1-3N0-1M0) who underwent breast conserving surgery were enrolled into the study. Thirty-six of these participants received 50 Gy of conventional irradiation in 25 fractions over 5 weeks to the whole breast with a sequential boost to the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Long-term survival data after CB as an adjuvant therapy in early-stage breast cancer are scarce. Kitwadee Saksornchai et al reported similar 10-year DFS (93.9% vs. 94.4%, p = 0.96) and OS (91.9% vs. 91.6%, p = 0.792) rates in the CB and SB groups, respectively [14]. Domenico Cante et al reported 10-year OS, cancer-speci c survival and DFS rates of 92.2% (95%CI 88.7%-93.4%), 99.2% (95%CI 96.7%-99.7%) and 95.5% (95%CI 91.2%-97.2%), respectively, corroborating this study [17].…”
Section: Discussionmentioning
confidence: 88%
“…Long-term survival data after CB as an adjuvant therapy in early-stage breast cancer are scarce. Kitwadee Saksornchai et al reported similar 10-year DFS (93.9% vs. 94.4%, p = 0.96) and OS (91.9% vs. 91.6%, p = 0.792) rates in the CB and SB groups, respectively [14]. Domenico Cante et al reported 10-year OS, cancer-speci c survival and DFS rates of 92.2% (95%CI 88.7%-93.4%), 99.2% (95%CI 96.7%-99.7%) and 95.5% (95%CI 91.2%-97.2%), respectively, corroborating this study [17].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, there was a significantly higher proportion of patients with a decline in pulmonary function at 2 years with conventional fractionation. The other randomized controlled trial from Thailand enrolled 73 patients and randomized them to conventional fractionation or 43.2 Gy to the whole breast and 52.8 Gy to the boost volume in 16 fractions [ 23 ]. With a median follow-up of more than 10 years, there were no significant differences in terms of local control, overall survival or late toxicity between the two arms.…”
Section: Discussionmentioning
confidence: 99%
“…The patient population includes a high proportion of low-risk patients; 93% of the patients were node-negative and 81% ER-positive. In all studies addressing HF with SIB, the local control rate was well above 95%, even in the two reports with ten-year follow-up [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the above rationales and evidence from various clinical trials, one may conclude that HFRT can be employed in BC patients, with non-inferiority clinical tumor control outcomes and toxicities, to shorten overall treatment course which is more convenient to the patients and cost saving to the patient and society. Of note, concomitant boost irradiation, though showed well tolerance and optimal disease control (31,32), including hypofractionation VAMT with simultaneous boost (33), was not used in our studies after breast irradiation. Additionally, it is important to note that sequential tumor bed boost of electron was employed in this retrospective study, further suggests the safety of the HFRT.…”
Section: Discussionmentioning
confidence: 99%